Unilateral Upper Cervical Cord Infarction: A Report of Two Cases with Mild Neurological Symptoms Accompanying a Small Ischemic Lesion Detected by Brain MRI - Manabu Wada; Hikaru Nagasawa; Yoshitaka Yamaguchi (Case Reports in Neurological Medicine)
Spinal cord infarction (SCI) is rare, difficult to diagnose, and often fails to be detected by diffusion-weighted imaging (DWI) of spinal cord magnetic resonance imaging (MRI). Because the clinical features of SCI can vary widely, diagnosis during the acute phase of SCI is often challenging for clinicians. Although SCI shares similar etiologies with cerebral infarction, the characteristics of SCI without vessel dissection remain largely unknown. We present two older patients with mild neurological symptoms who each presented with a small, unilateral, upper cervical cord lesion, which was detected by thin-section, coronal DWI of brain MRI. Both unilateral small lesions were localized in the right lateral funiculus, and each patient showed good prognosis. The anatomical findings suggested that the pial collateral network surrounding the cervical cord contributed to lesion formation. Small and localized lesions have been associated with mild neurological symptoms and better short-term prognosis. The present report indicated that the use of thin-section coronal DWI when performing brain MRI may be helpful for the diagnosis of small, unilateral, upper cervical cord infarctions.